Review on the Role of Host Immune Response in Protection and Immunopathogenesis during Cutaneous Leishmaniasis Infection - Teshager Dubie; Yasin Mohammed (Journal of Immunology Research)
Cutaneous leishmaniasis (CL) is a major public health problem worldwide and spreads to human via the bite of sand flies during blood meal. Following its inoculation, the promastigotes are immediately taken up by phagocytic cells and these leishmania-infected host cells produce proinflammatory cytokines that activate other immune cells and these infected host cells produce more cytokines and reactive nitrogen and oxygen species for efficient control of leishmania infection. Many experimental studies showed that resistance to infection with leishmania paraites is associated with the production of proinflammatory cytokines and activation of CD4+ Th1 response. On the other hand, vulnerability to this parasitic infection is correlated to production of T helper 2 cytokines that facilitate persistence of parasites and disease progression. In addition, some studies have also indicated that CD8+ T cells play a vital role in immune defense through cytokine production and their cytotoxic activity and excessive production of proinflammatory mediators promote amplified recruitment of cells. This could be correlated with excessive inflammatory reaction and ultimately resulted in tissue destruction and development of immunopathogenesis. Thus, there are contradictions regarding the role of immune responses in protection and immunopathogenesis of CL disease. Therefore, the aim of this paper was to review the role of host immune response in protection and its contribution to disease severity for CL infection. In order to obtain more meaningful data regarding the nature of immune response to leishmania, further in-depth studies focused on immune modulation should be conducted to develop better therapeutic strategies.